Corrected QT interval and GRACE score relationship in patients with non-ST segment elevation myocardial infarction - Cruz-Aragón, Guillermo; Márquez, Manlio F; Cueva-Parra, Angel; González-Pacheco, Héctor; Iturralde, Pedro; Nava, Santiago (Archivos peruanos de cardiología y cirugía cardiovascular, 2022)
The Global Registry of Acute Coronary Events (GRACE) prediction model stratifies patients with non-ST-segment elevation myocardial infarction (NSTEMI). Corrected QT interval (QTc) is not considered in this model. To evaluate the relationship between the QTc interval and the GRACE score in patients with NSTEMI. An observational, retrospective study was carried between 2016 and 2019. We included patients with diagnosis of NSTEMI, QTc intervals were calculated with Bazett's formula, and they were classified into 2 groups: a normal QTc interval (<440 ms) and prolonged (≥440 ms). According to the GRACE score they were classified in three ranges: low risk (≤109 points), intermedium (110 - 139 points) and high (≥140 points), we determined if there were a correlation between QTc interval and the GRACE score. A total of 940 patients with a diagnosis of NSTEMI were admitted in our institution, 634 met the inclusion criteria, there were 390 patients with normal QTc interval and 244 with a prolonged QTc interval. Patients with prolonged QTc were older (65.5 vs 61, p=0.001) with a lower proportion of males (71.7% vs 82.8%, p=0.001). An association was found between the GRACE score and the QTC interval, subjects with a normal QTc had a greater proportion of low and intermediate risk than those with a prolonged QTc (p=0.001). In NSTEMI patients, a normal QTc interval (<440 ms) is associated with a GRACE risk score of low or intermediate risk.